Wetlands and wintering waterbirds in Libya, January 2005 and 2006 - Smart, Mike; Essghaier, Mohamed F; Etayeh, Khaled; Hamza, Abdulmaula; Azafzaf, Hichem; Baccetti, Nicola; Defos du Rau, Pierre; Dlensi, Habib (Wildfowl, 2013)
x.